Effects of open-label placebos and self-monitoring in skin-picking disorder: a randomized crossover trial - Schienle, Anne; Wabnegger, Albert; Tanzmeister, Sandra (Frontiers in Psychiatry, 2025)
BackgroundSymptom reduction in skin-picking disorder (SPD) has previously been demonstrated using deceptive placebo treatments. However, to date, no study has investigated the effects of open-label placebos (OLPs) in this context.MethodFifty-two participants (mean age = 30 years, 85% female) with pathological skin-picking took part in a clinical crossover trial. The study included daily app-assisted symptom monitoring over two conditions: two weeks of OLP treatment (one pill per day) and two weeks without OLP treatment. No pharmacological treatment was given to reduce skin-picking during the trial. Symptom severity was measured using a disorder-specific questionnaire administered at baseline and after each two-week condition (OLP, no OLP) along with daily app ratings of symptom severity.ResultsBoth self-monitoring with and without OLP treatment resulted in reduced questionnaire scores compared to baseline. Daily app-based ratings showed a modest reduction (-3%) in the urge to engage in skin-picking and the time spent picking (-6 minutes/day) during the OLP condition. Participants generally adhered well to the pill-taking protocol, though many were skeptic toward the OLP treatment.ConclusionWhen used as a stand-alone-intervention, OLP treatment demonstrated only minimal effects beyond those achieved through self-monitoring.